A Case of Recurrent Erysipelas Caused by Streptococcus mitis Group. (30th May 2018) - Nygren, David; Nilson, Bo; Rasmussen, Magnus
Abstract : The aetiology of erysipelas remains poorly defined though beta-haemolytic streptococci are considered as the main causative pathogens. We describe a case of a 70-year-old woman with recurrent erysipelas in her left arm due to infection with streptococci of the mitis group. Her past medical history includes lymphoedema of the left arm secondary to lymph node dissection due to breast cancer surgery. On seven different occasions during a decade, she has presented a clinical picture of erysipelas and in three of them with Streptococcus mitis group bacteraemia. The results indicate that two cases were caused by Streptococcus mitis and one case was caused by Streptococcus oralis . This is, to our knowledge, the first reported cases of S. mitis and of S. oralis as the causative agents of erysipelas.